2017
DOI: 10.1136/neurintsurg-2016-012830
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous thrombolysis before endovascular therapy for large vessel strokes can lead to significantly higher hospital costs without improving outcomes

Abstract: BackgroundLimited efficacy of IV recombinant tissue plasminogen activator (rt-PA) for large vessel occlusions (LVO) raises doubts about its utility prior to endovascular therapy.PurposeTo compare outcomes and hospital costs for anterior circulation LVOs (middle cerebral artery, internal carotid artery terminus (ICA-T)) treated with either primary endovascular therapy alone (EV-Only) or bridging therapy (IV+EV)).MethodsA single-center retrospective analysis was performed. Clinical and demographic data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 31 publications
1
62
0
Order By: Relevance
“…In the present study, age and admission NIHSS were identified as prognostic factors on multivariate analyses but treatment allocation did not influence outcome. This is in agreement with a smaller single-center pilot study that examined the effects of bridging versus dEVT on outcome and found no such impact [18] as well as with several other retrospective studies [22,23,[33][34][35] and prospective registry data [20,21,24] that did not find differences in outcome between patients treated with bridging and those treated with dEVT. In contrast, other retrospective studies found lower mortality rates [23], lower symptomatic hemorrhage rates and higher reperfusion rates in patients treated with dEVT [36] while two meta-analyses on the subject found evidence for lowering mortality and severe disability rates with bridging [26,37].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the present study, age and admission NIHSS were identified as prognostic factors on multivariate analyses but treatment allocation did not influence outcome. This is in agreement with a smaller single-center pilot study that examined the effects of bridging versus dEVT on outcome and found no such impact [18] as well as with several other retrospective studies [22,23,[33][34][35] and prospective registry data [20,21,24] that did not find differences in outcome between patients treated with bridging and those treated with dEVT. In contrast, other retrospective studies found lower mortality rates [23], lower symptomatic hemorrhage rates and higher reperfusion rates in patients treated with dEVT [36] while two meta-analyses on the subject found evidence for lowering mortality and severe disability rates with bridging [26,37].…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, some studies included patients presenting up to 7 h from onset, while others only included patients presenting within 4 h from symptom onset. Moreover, while thrombectomy devices were used in most studies, others primarily used aspiration devices [19,23,33,38]. These differences probably account for the differences in outcomes observed across existing studies.…”
Section: Discussionmentioning
confidence: 78%
“…It is also important to note that the rate of patients with prestroke disability was not reported in most of the included studies, and was used as a potential confounder in the adjusted analyses by only 2 of the studies (see Supplementary Table 14). These trials are also expected to provide reliable data on the cost-effectiveness of BT compared to dMT, as only one small study to date with 90 patients has compared the hospital costs of BT compared to dMT, 45 with other studies assessing only the cost-effectiveness of BT compared to tPA monotherapy. 44 The ongoing trials SWIFT DIRECT (Solitaire with the Intention for Thrombectomy Plus Intravenous t-PA versus Direct Solitaire Stent-Retriever Thrombectomy in Acute Anterior Circulation Stroke; NCT03192332), DIRECT-MT (Direct Intra-arterial Thrombectomy in Order to Revascularize AIS Patients with Large Vessel Occlusion Efficiently in Chinese Tertiary Hospitals; NCT03469206), MR CLEAN-NO IV (Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands No IV), and DIRECT-SAFE (A Randomized Controlled Trial of Direct Endovascular Clot Retrieval versus Standard Bridging Thrombolysis with Endovascular Clot Retrieval; NCT03494920) will provide definitive answers on the potential clinical benefit of IVT pretreatment in LVO patients receiving MT.…”
Section: Discussionmentioning
confidence: 99%
“…These numbers increased to 13 (95% CI, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and 35 (95% CI, 18-464) when analysis was confined to M1 (proximal and distal) and ICA occlusions (SWIFT DIRECT trial cohort [Solitaire With the Intention for Thrombectomy Plus Intravenous t-PA Versus DIRECT Solitaire Stent-Retriever Thrombectomy in Acute Anterior Circulation Stroke], URL: http://www.clinicaltrials. gov.…”
Section: Number Needed To Treatmentioning
confidence: 99%
“…11 The latter is of interest because some studies found no difference in the rates of preinterventional reperfusion in patients treated with intravenous tPA compared with those without. 12,13 Because reperfusion of large vessel occlusion after intravenous tPA was shown to be time-dependent, 10 reperfusion may not occur early enough, that is, before the start of thrombectomy, and therefore in patients with direct access to endovascular treatment (ET), the prevalence, and extent of preinterventional reperfusion associated with intravenous tPA deserves further evaluation. The aim of this analysis was to assess the prevalence and quality of ultraearly preinterventional reperfusion in a predefined cohort of patients directly admitted to a comprehensive stroke center with immediate access to ET.…”
mentioning
confidence: 99%